2020
DOI: 10.1089/jpm.2019.0260
|View full text |Cite
|
Sign up to set email alerts
|

Multimorbidity and Opioid Prescribing in Hospitalized Older Adults

Abstract: Background: Multimorbidity and pain are both common among older adults, yet pain treatment strategies for older patients with multimorbidity have not been well characterized. Objectives: To assess the prevalence and relationship between multimorbidity and opioid prescribing in hospitalized older medical patients with pain. Methods: We collected demographic, morbidity, pain, and analgesic treatment data through structured review of the electronic medical records of a consecutive sample of 238 medical patients, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Research in Iceland showed that the majority of those who received benzodiazepine and/or Z-hypnotic prescriptions were multimorbid; and that those with multimorbidity were 15 times more likely than those without to be prescribed these drugs [ 24 ]. Another recent study focussing on older hospitalized patients in San Francisco, also reported that patients with higher multimorbidity burden tended to receive prescriptions of opioid analgesics at discharge, adjusted for sociodemographic variables, and pain [ 15 ]. Our results corroborate these findings, and also suggest that multimorbidity is not only associated with prescribing but also with long-term use of addictive medications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research in Iceland showed that the majority of those who received benzodiazepine and/or Z-hypnotic prescriptions were multimorbid; and that those with multimorbidity were 15 times more likely than those without to be prescribed these drugs [ 24 ]. Another recent study focussing on older hospitalized patients in San Francisco, also reported that patients with higher multimorbidity burden tended to receive prescriptions of opioid analgesics at discharge, adjusted for sociodemographic variables, and pain [ 15 ]. Our results corroborate these findings, and also suggest that multimorbidity is not only associated with prescribing but also with long-term use of addictive medications.…”
Section: Discussionmentioning
confidence: 99%
“…Very few studies have examined this topic specifically among older patients. Also, those conducted generally aimed to assess the likelihood of being prescribed potentially addictive medications rather than the effect of multimorbidity on prolonged drug use [ 15 , 16 ]. Moreover, insights regarding diseases that commonly coexist with prolonged use are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Our observation that more than 70% of discharges to a SNF were prescribed an opioid is higher than has been described in previous studies. Schear et al reported that 60% of patients in a sample of older adults with moderate to severe pain were prescribed an opioid on discharge 21 . In another study, Calceterra et al used a retrospective cohort study of opioid naive patients to quantify the frequency of opioid prescribing on discharge from a large safety‐net hospital and observed that 25% of patients received an opioid within 72 hours of hospital discharge 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Schear et al reported that 60% of patients in a sample of older adults with moderate to severe pain were prescribed an opioid on discharge. 21 In another study, Calceterra et al used a retrospective cohort study of opioid naive patients to quantify the frequency of opioid prescribing on discharge from a large safety-net hospital and observed that 25% of patients received an opioid within 72 hours of hospital discharge. 22 However, both of these studies included patients discharged to all locations compared to our study which focused on patients discharged to a SNF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation